2021
DOI: 10.26599/bsa.2021.9050023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the malignant potential of gliomas using diffusion-weighted and gadolinium-enhanced magnetic resonance imaging

Abstract: Objective: This study aimed to determine whether the apparent diffusion coefficients (ADCs) determined by diffusion-weighted imaging (DWI) of magnetic resonance imaging (MRI) could facilitate the malignancy grading of various gliomas. Methods: Sixty patients with a primary cerebral glioma underwent diffusion-weighted and gadolinium-enhanced (Gd) T1-weighted MRI using a 1.5-T MRI scanner. Scoring was performed based on signal intensities on DWI and Gd images. The mean and minimum ADC values were calculated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Experiments have shown that color Doppler ultrasound (US) and magnetic resonance imaging (MRI) and alpha-fetoprotein (AFP) imaging are currently used for prenatal screening for placenta accreta. Among them, AFP is not specific because of its many influencing factors and can only be used as a screening method, while the clinical reports of US and MRI diagnosis of placenta accreta are mostly used alone [ 10 ]. Zhi et al stated that the current prenatal diagnosis of placenta accreta mainly relies on two-dimensional color ultrasound, three-dimensional ultrasound Doppler ultrasound, three-dimensional color power Doppler ultrasound and magnetic resonance imaging (MRI), and other methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiments have shown that color Doppler ultrasound (US) and magnetic resonance imaging (MRI) and alpha-fetoprotein (AFP) imaging are currently used for prenatal screening for placenta accreta. Among them, AFP is not specific because of its many influencing factors and can only be used as a screening method, while the clinical reports of US and MRI diagnosis of placenta accreta are mostly used alone [ 10 ]. Zhi et al stated that the current prenatal diagnosis of placenta accreta mainly relies on two-dimensional color ultrasound, three-dimensional ultrasound Doppler ultrasound, three-dimensional color power Doppler ultrasound and magnetic resonance imaging (MRI), and other methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…10 Another study also found that a high signal intensity on DWI is helpful in diagnosing the malignant potential of gliomas, and the qualitative evaluation of the D score from DWI properly reflected the pathological grade of gliomas. 12 HGG has characteristics contrary to those of LGG, which is dense and actively growing with a high ratio of nucleus to the cytoplasm and higher intracellular water content than extracellular, so HGG shows high signal intensity on DWI. 13 However, traditional DWI cannot accurately display the actual movement of water molecules since it ignores the effects of capillary microcirculation.…”
Section: Discussionmentioning
confidence: 94%
“…Magnetic Resonance Imaging (MRI) plays a crucial role in diagnosing brain tumors and is also extensively used in detecting various neurodegenerative conditions. 10 Leveraging MRI scan data has proven invaluable in glioblastoma prognosis and survival model studies. 11 Therefore, studies tried using MRI images as a survival predictor for the deep learning models.…”
Section: Introductionmentioning
confidence: 99%